Nie taki wilk straszny… O edukacji ekologicznej w kontekście bajki Wilk Ambaras Tomasza Samojlika i jej wpływie na kształtowanie postaw proekologicznych dzieci i młodzieży względem wilków - Naplocha , Anna (Studia Edukacyjne, 2019)
This article deals with the issue of achieving the goals of ecological education in the context of the fable The Wolf Called Ambaras by Tomasz Samojlik and its influence on shaping pro-ecological attitudes of children and adolescents towards wolves. The fable The Wolf Called Ambaras by Tomasz Samojlik is part of the literature trend promoting pro-ecological attitudes within the framework of ecological education. The main educational goal included in the story of the fable treating the adventures of the young wolf is to provide young readers and their parents the knowledge about the wolves’ life as well as public awareness of the need to protect the wolf by shaping positive attitudes of people towards this predator. Helpful in this assumption is taking up the problem of overthrowing negative stereotypes about wolves, on which the form of answers as well as attemption of demythologizing them are individual scenes of the fable. The plot of the analyzed fable attempts to answer the three main allegations of people towards wolves, which often appear in social, political and ecological discourse: the issue of wolves attacks on people, the impact of wolves hunting on forest game population and the public perception of a wolf as a bad animal, one unnecessary in the ecosystem. In addition, the bibliotherapeutic character of the fable was indicated. Through identificaiton with the character of the fable, readers can overcome their own fears related to their weaknesses and complexes based on the desensitization.